Dynamic weight-bearing assessment of pain in knee osteoarthritis: construct validity, responsiveness, and interpretability in a research setting. Issue 1 (December 2016) - Klokker, Louise; Christensen, Robin; Wæhrens, Eva; Bandak, Elisabeth; Bartholdy, Cecilie; Bliddal, Henning; Henriksen, Marius
Abstract Background The Osteoarthritis Research Society International (OARSI) has suggested to asses pain after specific activities consistently in clinical trials on knee OA. The Dynamic weight-bearing Assessment of Pain (DAP) assesses pain during activity (30 s of performing repeated deep knee-bends from a standing position). The purpose of this study is to evaluate the construct validity, responsiveness, and interpretability of the DAP for knee osteoarthritis (OA). Methods One-hundred participants with knee OA were tested twice each with the DAP, the Knee injury and Osteoarthritis Outcome Score (KOOS), six-minute-walk-test (6MWT), and 6-min-walk-test with subsequent pain rating (6MWTpain), and once with a transition questionnaire (TRANS-Q) for the patient-reported change in pain after 12 weeks of exercise. Construct validity (baseline-scores) and responsiveness (change-scores) were estimated by Spearman Correlation Coefficients. We hypothesized that no correlations would be excellent (<0.7) (divergent validity), except for the 6MWTpain (convergent validity). The TRANS-Q was used for interpreting the DAP change-scores in terms of responsiveness and Minimal Important Change (MIC). Results Divergent validity with the KOOS subscales (r = −0.31 to–0.45) and the 6MWT (r = −0.25) was supported. Convergent validity with the 6MWTpain was not supported (r = 0.54). The DAP change-scores corresponded to patient-reported change in pain (TRANS-Q), while correlations with change-scores on the other instruments were <0.35. The MIC was 2.4 DAP points. Conclusions The DAP possesses divergent validity compared to other instruments for knee OA, supporting the potential for this new way of assessing pain directly during activity. Importantly, the DAP change-scores correspond to patient-reported changes in pain, showing responsiveness. A change of 2.4 or more can be interpreted as clinically relevant. The DAP is a promising alternative to using 'pain on walking' as a clinical trial inclusion criterion/outcome.